The IT strategy divide: Professional practice and academic debate - Rolf Alexander Teubner; Alexander Pellengahr; Martin Mocker (Westfälische Wilhelms-Universität Münster, European Research Center for Information Systems (ERCIS), 2012)
Information Technology (IT) strategy is a top-priority issue in practice. However, despite its practical relevance, research on IT strategy has been limited so far. With respect to the definition of an IT strategy and its scope, there are a number of ad hoc recommendations and a few conceptual models with little scientific backing. In particular, latest research indicates a gap between the academic discussion on IT strategy and how IT strategy is perceived in practice. Taking this as a motivation, our research sets out to uncover in more detail the concerns and the notions of IT strategy prevalent in practice. This paper reports on the results of a qualitative research project which included interviews with IT strategy professionals from twelve mid-size to large companies in German speaking countries. It compares the experts' IT strategy practice with the concerns and perceptions that dominate research and the academic discussion. Our study uncovers striking differences between the academic debate on IT strategy and the concerns IT strategy professional look upon as being important. First of all, we found that professionals are concerned with IT strategy on two different levels, the corporate level and the business unit level strategy. Academics, in contrast, look at IT strategy mostly from a business unit and departmental level. Irrespective of the differences in the level of IT strategy, the strategy concerns focused on in academia differ substantially from those that our professionals were most interested in. The focus of the academic discussion is on IT-based competitive advantages and stresses the role of information as strategic resources, while practitioners are most concerned with decisions on IT infrastructure, IT architecture and standards. The paper at hand does not only analyse the differences but also takes a closer look at the reasoning of academics and professionals for looking upon certain IT issues as 'strategic'. Both, the IT strategy concerns raised by our professionals and the rationales used provide valuable input for future research and theory development.
Keywords: 650; IT strategy; IT strategy concerns; IT strategy content; strategic IT decisions; strategic information systems planning (SISP); IT strategy practice